Economic evaluation of low-carbon steelmaking via coupling of electrolysis and direct reduction. (15th December 2021) - Jacobasch, Eric; Herz, Gregor; Rix, Christopher; Müller, Nils; Reichelt, Erik; Jahn, Matthias; Michaelis, Alexander
Abstract: The transition from fossil-based primary steel production to a low-emission alternative has gained increasing attention in recent years. Various schemes including Carbon Capture and Utilization (CCU) and Carbon Direct Avoidance (CDA) via hydrogen-based as well as electrochemical routes have been proposed. With multiple technical analyses being available and technical feasibility being proven by first pilot plants, pathways towards commercial market entry are of increasing interest. While multiple publications on the economic feasibility of CCU are available, data on CDA approaches is scarce. In this work an economic model for the quantification of production cost as well as CO2 emission mitigation cost is presented. The approach is characterized by a seamless integration with a flowsheet-based process model of a direct reduction-based crude steel production plant detailed in a previous work and allows for the investigation of multiple economic aspects. Firstly, the gradual transition from the natural gas-based state-of-the-art direct reduction towards a fossil-free hydrogen-based reduction is analyzed. Furthermore, a comparison between the more mature technology of low-temperature electrolysis and a potentially more efficient solid oxide electrolysis (SOEL) is given, highlighting the potential of SOEL technology. The conducted forecast to 2050 shows that SOEL-based CDA offers lower production cost when technological maturity is reached. Based on the results of the economic assessment possible legislative support mechanisms are studied, showing that legislative actions are necessary to allow for market entry as well as for sustainable and economically feasible operation of fossil-free direct reduction plants.